2001
DOI: 10.1016/s0735-1097(01)01183-4
|View full text |Cite
|
Sign up to set email alerts
|

New diagnostic criteria for diabetes and coronary artery disease: insights from an angiographic study

Abstract: In patients with type 2 diabetes, those with 7.0 mM/L < or = fasting plasma glucose < 7.7 mM/L have a slightly greater prevalence of mildly severe lesions that may partly explain their higher cardiovascular event rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
3
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(103 citation statements)
references
References 27 publications
5
89
3
6
Order By: Relevance
“…Our study is the first that used established scores of the atherosclerotic burden determined by angiography in a large study population. The present findings of more severe coronary artery disease with higher atherosclerotic scores on angiography in patients with diabetes are confirmed in two recently published investigations by Ledru et al [14] and Natali et al [22], as well as two epidemiological studies [23,24] that also found a more severe and diffuse coronary atherosclerosis in diabetic patients. The higher rates of diffuse disease found in these studies is in line with the higher frequency of three-vessel disease and the presence of peripheral coronary artery disease in our study population.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our study is the first that used established scores of the atherosclerotic burden determined by angiography in a large study population. The present findings of more severe coronary artery disease with higher atherosclerotic scores on angiography in patients with diabetes are confirmed in two recently published investigations by Ledru et al [14] and Natali et al [22], as well as two epidemiological studies [23,24] that also found a more severe and diffuse coronary atherosclerosis in diabetic patients. The higher rates of diffuse disease found in these studies is in line with the higher frequency of three-vessel disease and the presence of peripheral coronary artery disease in our study population.…”
Section: Discussionsupporting
confidence: 90%
“…However, there is some controversy in this regard in the literature. Whereas Ledru et al [14] found similar results as in our registry, there are other reports that could not demonstrate a significant difference in the severity of coronary artery disease between diabetic patients and patients without diabetes [15,20,21]. The much smaller number of patients investigated compared to the present study may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…36 Another possibility is the higher prevalence of glucose intolerance in our female population, a condition preceding frank diabetes. 37 Increasing evidence shows that the gender-specific difference in CHD mortality decreases with age, and women with MS experience the greater risk. 38 Of course, we have observed a population in which a natural selection has occurred in the previous decades, a selection that is notoriously more important in men, more prone to succumb to MS.…”
Section: Discussionmentioning
confidence: 99%